Parental Guidance, Teacher Performance and Learning Achievement - Muhammad Shofi Al Amin; Muh. Amiruddin Salem; Rahmad Bala (The Indonesian Institute of Science and Technology Research, 2022)
Guidance is one factor that can support the smooth learning of a child. Another factor that is also important in a child's learning process is the teacher's performance. If it can be done well, the level of student achievement will also be good. This study aims to analyze the influence of parental and teacher performance on student achievement, either partially or jointly. This type of research is ex post facto analysis, which is done to find out what had happened and then pulled back through the data to determine the factors that precede or the causes of the incident. This study uses a quantitative approach that is research that requires the respondent to be made objects on the questionnaire, and the results will be analyzed using statistics—analysis of data using multiple regression analysis. The study's results generally showed that parental and teacher performance significantly influences student achievement. In particular, the results of the research show that the guidance of parents does not have a significant effect on student achievement. In contrast, teacher performance has a significant impact on student achievement. With these results, it can be argued that collectively, parental and teacher performance substantially affects student achievement.